Effect of nanoclay and silica on mechanical and morphological properties of jute cellulose polyethylene biocomposites - Md. Rezaur, Rahman; Md Mizanur, Rahman; Sinin, Hamdan; Md Faruk, Hossen; Chang, Josephine Hui Lai; Fui, Kiew Liew (John Wiley and Sons Ltd, 2017)
In this study, jute cellulose/polyethylene (PE) biocomposites were prepared using a hot press machine. Silica and nanoclay act as reinforcing agents in the composite system. The effects of clay and silica addition on the mechanical, thermal, and morphological properties of jute cellulose/PE biocomposites with different fiber loadings (5, 10, 15, and 20 wt %) were investigated. The biocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, and thermogravimetric analysis. The mechanical properties were investigated using a universal testing machine. From FTIR results, it indicates that the CO stretching vibration had disappeared, while the intensity of peaks at 1718 and 1716 cm−1 appeared after addition of silica. The better interfacial bonding between jute cellulose/PE/silica biocomposites are reflected in the enhancement of the mechanical properties as well as thermal stability. The tensile strength and modulus had shown the highest values as well as higher activation energy for thermal decomposition. The surface area analysis result showed that the jute cellulose/PE/silica biocomposites have higher surface area and pore volume with less pore size. The manufactured biocomposites can be used in interior and exterior applications as well as a construction material.